The natural diet composition of young piglets suggests an overlook of fibre and food structure in farmed suckling piglets - Renjie Yao; Hubèrt M. J. van Hees; An Cools; Sebastián A. Ballari; Dominiek Maes; Geert P. J. Janssens (Porcine Health Management)
Abstract Background The often disappointing intake of creep feed by suckling piglets coincides with a limited ability to cope with challenges such as weaning diarrhoea. Investigating the dietary nutrient profile of piglets (Sus scrofa) in the wild may help to improve nutrition for farmed piglets. This study was conducted to analyse the stomach content of feral piglets and their farmed counterparts, and to compare them with the composition of commercial creep feeds. Forty feral piglets (4.6 ± 1.4 kg) living in a wild herd were tracked and legally hunted in the Bahía Samborombón (Buenos Aires, Argentina). Their gastric contents were collected for analysing macronutrients. Twenty-eight farmed suckling piglets of similar ages were sourced from a Dutch research farm, and their stomach contents were collected and pooled into fourteen samples with the same procedure for comparison. Additionally, the composition data of twenty-five commercial feeds was also collected. Results A higher dry matter content was observed in the farmed piglets’ stomachs (233 vs. 148 g/kg, P < 0.05). The gastric crude protein concentration was similar between both groups but the crude fat concentration was higher in the stomach of farmed animals (525 vs. 238 g/kg DM, P < 0.05), while feral piglets consumed more ash and fibre (P < 0.05). A similar concentration of non-fibrous carbohydrates (NFC) on metabolizable energy basis was observed by calculation through the NRC’s guideline (P > 0.05). Within the fibre content, significantly greater concentrations of neutral detergent fiber (NDF), acid detergent fiber (ADF) and acid detergent lignin (ADL) were observed in the stomach of feral piglets than in those of farmed piglets (282 vs. 36 g/kg, 158 vs. 9 g/kg DM, 53 vs. 3 g/kg DM, respectively, P < 0.05). Similar protein concentrations were observed between the gastric content of feral piglets and creep feed, while significantly higher crude ash and crude fat concentrations were found in feral piglets’ consumption (P < 0.05). Conclusion In conclusion, piglets in natural conditions consume much more fibre—from coarse plant material—compared to farmed piglets receiving creep feed. Although technical performance is distinctly different between nature and farm, it raises the question whether suckling piglets under farming conditions would benefit from a more fibrous and coarser creep feed.